Performance Improvement through Strengthening Organizational Culture, Interpersonal Communication, Self-Efficacy, and Job Satisfaction - Nina Dwiastuty; Sri Setyaningsih; Lina Novita (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The purpose of this study is to improve performance through strengthening organizational culture, interpersonal communication, self-efficacy, and job satisfaction. The method used in this research is quantitative, with path analysis, then continued with SITOREM analysis to analyze the variable indicator items that affect performance. The results of this study are that there is a direct influence of organizational culture, interpersonal communication, self-efficacy, and job satisfaction variables on performance; there is a direct influence of organizational culture, interpersonal communication, and self-efficacy on job satisfaction; there is an indirect influence of organizational culture, interpersonal communication, and self-efficacy on performance through job satisfaction.